2012
DOI: 10.1063/1.3687184
|View full text |Cite
|
Sign up to set email alerts
|

A statistical exploration of multiple exciton generation in silicon quantum dots and optoelectronic application

Abstract: We have carried out an investigation of multiple exciton generation (MEG) in Si quantum dots (QDs) and its application in optoelectronic devices. A simple yet effective statistical model has been proposed based on Fermi statistical theory and impact ionization mechanism. It is demonstrated that the MEG efficiency depends on both the radius of Si QDs and the energy of incident photons, with the MEG threshold energy in the range of ∼2.2–3.1 Eg depending on the dot radius. While limited improvement has been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…(2). 30 The constant 1.15 eV is the Eg value for bulk Si. 31 D −1 36 is the spatial localization of the electrons and holes, and D −1 indicates an increasing size dependent Coulomb attraction.…”
Section: Resultsmentioning
confidence: 99%
“…(2). 30 The constant 1.15 eV is the Eg value for bulk Si. 31 D −1 36 is the spatial localization of the electrons and holes, and D −1 indicates an increasing size dependent Coulomb attraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, its inherent indirect band gap properties have limited its use in photovoltaic and light emitting diode applications. When the dimensions of Si nanoparticles (NPs) become comparable or smaller than Bohr radius of a bulk exciton ($4 nm for Si), [1][2][3][4] they undergo a remarkable transition from indirect to direct band gap semiconductor. 5 Under such conditions, band-to-band radiative recombination (rather than phonon-assisted indirect transitions) begins to dominate Si-NPs' luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that carrier multiplicationa process in which absorption of a single high-energy photon creates multiple electron–hole pairs (excitons)occurs efficiently in Si NCs. This holds a great potential for highly efficient photovoltaic conversion exceeding the Shockley–Queisser limit . Carrier multiplication in Si NCs also has a potential for application in ultraviolet detectors . However, in a strong quantum confinement regime, electron–electron coupling is sufficiently enhanced in comparison to the electron–photon coupling.…”
Section: Introductionmentioning
confidence: 99%